Efficacy of several Salmonella vaccination programs against experimental challenge with Salmonella gallinarum in commercial brown layer and broiler breeder hens - Paiva, JB de [UNESP]; Penha Filho, RAC [UNESP]; Argüello, YMS [UNESP]; Silva, MD da [UNESP]; Gardin, Y; Resende, F; Berchieri Junior, A [UNESP]; Sesti, L (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
The protective effect of various Salmonella vaccines regimens against an experimental Salmonella Gallinarum challenge (SGNalr strain at 12 wk of age) was evaluated in two experiments. In Experiment 1 commercial brown layers were vaccinated according to one of the following programs: (i) two doses of a SE bacterin (Layermune SE; group 1); (ii) a first dose of a live SG9R vaccine (Cevac SG9R) followed by a SE bacterin (Layermune SE; group 2); (iii) one dose of each of two different multivalent inactivated vaccines containing SE cells (Corymune 4 & Corymune 7; group 3) or (iv) not vaccinated (group 4). In Experiment 2, broiler breeders were given the same vaccination treatments except for the group vaccinated with the multivalent vaccines. Overall, in both experiments, all vaccination schemes were effective in reducing mortality after challenge with a SG field strain. Primary vaccination with an initial dose of a live SG9R vaccine followed some weeks later by a dose of an inactivated SE bacterin was the most effective (p<0.05) vaccination program against mortality induced by field SG experimental challenge in both experiments. In conclusion, Salmonella vaccination programs containing SE bacterins alone or in combination with a live SG9R vaccine are effective in preventing mortality induced by infection of field SG. Nevertheless, it is important to emphasize that any vaccination program against any Salmonella serotype will only be effective if it is part of a sound and comprehensive biosecurity program designed for Salmonella control in poultry farms.
Keywords: Fowl Typhoid; killed Salmonella vaccines; live Salmonella vaccines; Salmonella Gallinarum; Salmonella Gallinarum challenge